2015
DOI: 10.1002/cphc.201500780
|View full text |Cite
|
Sign up to set email alerts
|

Photon Harvesting in Sunscreen‐Based Functional Nanoparticles

Abstract: The ultraviolet light component in the solar spectrum is known to cause several harmful effects, such as allergy, skin ageing, and skin cancer. Thus, current research attention has been paid to the design and fundamental understanding of sunscreen-based materials. One of the most abundantly used sunscreen molecules is Avobenzone (AB), which exhibits two tautomers. Here, we highlight the preparation of spherically shaped nanoparticles from the sunscreen molecule AB as well as from sunscreen-molecule-encapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Despite the fact that AB has practical importance as an UVA filter, complete understanding of its photophysics and photochemistry is still missing due to solvent-dependent multiple relaxation pathways. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] AB is a b-dicarbonyl compound liable to keto-enol tautomerization. Many theoretical and experimental studies provided evidence that in the ground state the chelated enol form is favored due to the intramolecular hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that AB has practical importance as an UVA filter, complete understanding of its photophysics and photochemistry is still missing due to solvent-dependent multiple relaxation pathways. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] AB is a b-dicarbonyl compound liable to keto-enol tautomerization. Many theoretical and experimental studies provided evidence that in the ground state the chelated enol form is favored due to the intramolecular hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorophore-doped conjugated PNPs are established to be alternative next-generation luminescence sources due to brighter luminescence properties, easy solution-based synthetic procedures, greater photostability, and extremely nontoxic behavior. Considering the advantages of PNPs, sunscreen-based polymer nanomaterials would be a potential for healthcare applications . Emphasis has been given to the role of particle size and population of the dye molecules inside of the PNPs in rotational dynamics and particle brightness.…”
mentioning
confidence: 99%
“…Considering the advantages of PNPs, sunscreen-based polymer nanomaterials would be a potential for healthcare applications. 117 Emphasis has been given to the role of particle size and population of the dye molecules inside of the PNPs in rotational dynamics and particle brightness. Time-resolved photoluminescence spectroscopic analysis on the cascade energy transfer for white light and singlet oxygen generation in multiple fluorophore-containing PNP systems is given.…”
mentioning
confidence: 99%
“…Mandal et al 26 investigated the photophysical properties and photostability of AVO in three different systems: a solution of tetrahydrofuran (THF) and AVO; a dispersion of AVO nanoparticles in water; and PMMA nanoparticles (loaded with AVO) dispersed in water. The authors showed that the encapsulation of AVO in PMMA by the precipitation technique restricted the keto‐enol transformation.…”
Section: Introductionmentioning
confidence: 99%